1992
DOI: 10.1016/s0006-3495(92)81855-6
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional model of calcium waves reproduces the patterns observed in Xenopus oocytes

Abstract: Biological excitability enables the rapid transmission of physiological signals over distance. Using confocal fluorescence microscopy, we previously reported circular, planar, and spiral waves of Ca2+ in Xenopus laevis oocytes that annihilated one another upon collision. We present experimental evidence that the excitable process underlying wave propagation depends on Ca2+ diffusion and does not require oscillations in inositol (1,4,5)trisphosphate (IP3) concentration. Extending an existing ordinary differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 18 publications
4
33
0
Order By: Relevance
“…Because the effective diffusion constant for Ca2+ is much smaller than that of IP3 (9), it has been argued that diffusion of Ca2+ can explain the speed of the wave (10), and recently mathematical models have been used to explore the role of diffusion in these waves (4,11,12). Here we report calculations with a realistic model of IP3-induced Ca2+ oscillations (13), which when combined with the diffusion of Ca2+ and IP3 can generate wave trains that are primarily kinematic in nature-i.e., they do not require bulk movement of Ca2+ (14-16).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the effective diffusion constant for Ca2+ is much smaller than that of IP3 (9), it has been argued that diffusion of Ca2+ can explain the speed of the wave (10), and recently mathematical models have been used to explore the role of diffusion in these waves (4,11,12). Here we report calculations with a realistic model of IP3-induced Ca2+ oscillations (13), which when combined with the diffusion of Ca2+ and IP3 can generate wave trains that are primarily kinematic in nature-i.e., they do not require bulk movement of Ca2+ (14-16).…”
Section: Introductionmentioning
confidence: 99%
“…way, and Clapham, Lechleiter and colleagues (4) have documented a rich variety of dynamical patterns and spiral waves generated by nonhydrolyzable analogues of IP3. In hamster eggs, experiments have demonstrated that inactivating the IP3 receptor/Ca2+ channel (IP3R) with monoclonal antibodies is sufficient to eliminate fertilization-induced Ca2+ waves (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Adapting the idea of the superficial buffer barrier (SBB) introduced in smooth muscle cells to endothelial cells, we studied whether under weak stimulation with a physiological bradykinin concentration (< 2 nmol l¢; Linz, Wiemer & Sch olkens, 1996) or sodium fluoride, vectorial Ca¥ release towards the cell membrane from superficial endoplasmic reticulum (SER) occurs which is restricted to a discrete subplasmalemmal area by plasma membrane Na¤-Ca¥ exchange activity. Subplasmalemmal [Ca¥] ([Ca¥]sp) and bulk [Ca¥] ([Ca¥]b) were simultaneously recorded using Calcium Green-1 to measure predominantly [Ca¥]b (Girard, L uckhoff, Lechleiter, Sneyd & Clapham, 1992) and FFP-18 to estimate changes in [Ca¥]sp (Etter et al 1996). Distribution of endothelial ER was investigated using laser scanning (confocal) and deconvolution microscopy.…”
mentioning
confidence: 99%
“…In cultured osteoblasts, Calcium Green C 18 appears to be localized along the entire plasma membrane, except for regions associated with the coverslip. Ca 2ϩ specificity is indicated since the calcium greens have been shown to preferentially bind calcium (Girard et al, 1992). Further, little fluorescence was observed under the chosen confocal settings when cells were bathed with RCBSS, which intrinsically contained trace amounts of Ca 2ϩ .…”
Section: Discussionmentioning
confidence: 99%